IMPACT MICROFINANCE CREDIT ACCESS TO IMPROVE HOUSEHOLD WELFARE : EVIDENCE LONGITUDINAL DATA - Prihantono, Gigih . (FEB Universitas Sam Ratulangi Manado, 2017)
Evidence on microfinance services these days ironically shows a great preference for savings products rather than credit products by households. For some authors, this phenomenon is explained by the fact that microfinance products, and especially loans, from formal microfinance institutions do not fit the households demand. This paper first presents evidence on the observed phenomenon in Indonesia microfinance sector. Second, it analyses the Indonesia credit market so as to understand the determinants of the choice for credits from formal sources versus informal sources. The results reveal the size of the loan, agricultural purpose, the geographical area where households live and ethnicity as factors influencing the choice for formal sources.Â Keywords : microfinance Credit access,household